Policy Brief—Encouraging Innovation that Protects Environmental Systems: Five Policy Proposals. (19th January 2018) - Hepburn, Cameron; Pless, Jacquelyn; Popp, David
Abstract: Human innovations have created widespread human prosperity. However, they are also threatening the global environmental systems on which our economy and civilization depend. The likely solutions to these challenges—such as the transition to clean energy systems—will require yet more innovation. This article presents five policy proposals that would support more innovation of the environmentally beneficial kind and less innovation of the environmentally harmful kind. We argue that the appropriate portfolio of innovation policies for protecting global environmental systems should include pricing natural capital; providing and targeting research and development (R&D) support towards environmentally beneficial innovations, based on the evidence acquired through more rigorous experimental designs; providing early-stage deployment subsidies for environmentally friendly technologies in particular circumstances; supporting collaborative R&D to leverage complementary capabilities in various types of organizations; and reducing barriers to private sector environmental finance. Policies in these five areas could help redirect innovation towards environmentally friendly economic activities.